PERANAN GURU DALAM PEMBELAJARAN FIKIH PADA MURID KELAS XI MAN 1 KOTA MAKASSAR - Safwan Ariyadi Kusuma; M Shabir U; Awaliah Musgamy; Syahruddin; Idah Suaidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the role of teachers in fiqh learning for eleventh-grade students at MAN 1 Makassar City, identify supporting and inhibiting factors, and analyze strategies used by teachers to overcome learning obstacles. This research employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving fiqh teachers, students, and school administrators. The results showed that teachers played multiple roles, including educators, instructors, motivators, facilitators, and role models. Supporting factors include structured curriculum, teacher competence, and religious school activities, while inhibiting factors involve limited learning facilities and diverse student abilities. Teachers addressed these challenges through adaptive teaching strategies, optimizing learning media, and improving classroom management. This study highlights the importance of maximizing teacher roles to improve students’ understanding and practice of Islamic teachings.